The Anxiety of Language Learning and Language Skills: Conceptual Problems and Helpful Ideas to the Study of English as a Foreign Language - Asti Gumartifa (Universitas PGRI Yogyakarta, 2020)
Ignoring the fact of anxiety as second language learning is a new issue in the process of acquiring an international language. Teachers seldom recognize anxious students and instead assign a lack of other factor discussions of students’ low accomplishments. in acquiring the English language. This research intends to assist literature completely on the classification of second language and language skills anxiety. The overviews of decreasing or giving solutions about students’ anxiety in various potential aspects occur. Further items of the questionnaire in measuring students’ anxiety in terms of the Foreign Language Classroom Anxiety Scale mentioned. Utilizing qualitative study presents a review in the classroom that aimed to investigate the variations of anxious students. This study finding and solution also describe analysis approaches and examines the educational effects of the result.